TRADISI PAWANG HUJAN DENGAN AYAT-AYAT AL-QUR’AN “Di Desa Jangkat Kecamatan Ulu Rawas Kabupaten Musi Rawas Utara (Studi Living Qur’an)” - Humayrah, Siti (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2023)
The background of this research is the existence of verses from the Koran that live in the midst of the community, precisely in the village of Jangkat, sub-district of Ulu Rawas, district of North Musi Rawas, South Sumatra. This rain charmer has been carried out by the community for generations, using the recitation of verses from the Qur'an, verses of the Koran used by the rain charmer such as surah Al-Ikhlas, Yasin and the last verse of surah Al-Baqarah. Which tools or materials are used such as salt and gravel.The researcher used a qualitative research type with a descriptive analysis approach, the writer used field research in the form of non-participant observation, the writer used observation collection techniques to produce data that corresponds to reality. Interviews (interviews) to obtain information from sources about how the rain charmer's tradition with verses from the Qur'an, documentation to add data in the form of photos and sound recordings. The researcher can conclude that: After seeing and analyzing the procedures carried out by the rain charmers which are carried out in a ritual manner and in which there are supernatural elements. The people of Jangkat village, Ulu Rawas sub-district, still believe that the rain handler is able to control rain by using verses from the Koran such as Surah Al-Ikhlas, Yasin, and Al-Baqarah. The conclusion is that the people of the village of Jangka, Ulu Rawas District, still believe in the rain charmer tradition with verses from the Koran.